Religious Understanding of Nature and Influence of Geographical Environment on Shaping Religious Beliefs and Practices within Christianity and Islam - Sayem, Md. Abu (KARSA Journal of Social and Islamic Culture, 2018)
The present paper connects nature with religious understanding in regard to Christianity and Islam. Many studies show that religious beliefs and practices were shaped and reshaped, to many points, being influenced by a specific geographical environment. So, the paper aims to focus how nature serves continuously in generating human thought, feeling and experience especially with respect to religions. By correlating some verses of the Bible and the Quran alongside some interpretations by religious scholars, the paper attempts to explore why religious understanding of nature seems significant for preventing the natural environment from further degradation caused by uncontrolled human activities in nature. In so doing, it will be an effort to enrich the current discussions relating to religions and natural environment.